2019
DOI: 10.14341/probl10070
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen metabolism, lifetime methylation disorders, and breast cancer

Abstract: Oncogenesis can be caused by an increase in the activity of genes responsible for initiating tumor growth in stem or progenitor cells, as well as a reduction in the functioning of suppressor genes. Endogenous estrogen exposure is associated with an increased risk of breast cancer in both pre- and postmenopausal women. The most important step in the understanding of the pathogenesis of breast cancer was the development of the theory of the switching of estrogen’s effect from hormonal to genotoxic, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…16α-OHE1 is produced by the hydroxylation reaction on the 16th carbon atom of estrogen, and the CYP3A4 enzyme exerts a significant effect on the process of C-16 hydroxylation [ 17 ]. Chagay reported that 16α-OHE1 was highly expressed in estrogen-dependent breast cancer cells [, they showed that 16α-OHE1, a metabolite of estrogen, supports the proliferation of breast cancer cells, which may be associated with the subsequent development of cancer [ 18 ]. The measurement of estrogen and estrogen metabolites in urine of premenopausal women displayed that a higher concentration of 16α-OHE1 increased the risk of breast cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…16α-OHE1 is produced by the hydroxylation reaction on the 16th carbon atom of estrogen, and the CYP3A4 enzyme exerts a significant effect on the process of C-16 hydroxylation [ 17 ]. Chagay reported that 16α-OHE1 was highly expressed in estrogen-dependent breast cancer cells [, they showed that 16α-OHE1, a metabolite of estrogen, supports the proliferation of breast cancer cells, which may be associated with the subsequent development of cancer [ 18 ]. The measurement of estrogen and estrogen metabolites in urine of premenopausal women displayed that a higher concentration of 16α-OHE1 increased the risk of breast cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%